Vacuum optomechanics of optically levitated objects. (March 2020) - Brzobohaty, Oto; Damkova, Jana; Svak, Vojtech; Siler, Martin; Jakl, Petr; Simpson, Stephen; Marago, Onofrio; Donato, Maria-Grazia; Filip, Radim; Zemanek, Pavel
Abstract: We will introduce to vacuum levitation of objects and present our recent theoretical and experimental results related to the behaviour of micro- and nanoparticles placed into nonlinear optical potentials in underdamped regime.